2021
DOI: 10.3897/folmed.63.e59406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress Biomarkers in Patients with Henoch-Schönlein Purpura

Abstract: Introduction: Henoch-Schönlein Purpura (HSP) is a systemic vasculitic syndrome characterized by non-thrombocytopenic purpura, arthritis/arthralgia, abdominal pain, and glomerulonephritis. The pathogenesis of HSP has not been clearly identified. Oxidative damage has a role in the pathogenesis of most cases. Aim: This study aimed to evaluate changes of oxidative stress by studying parameters like superoxide dismutase (SOD), catalase (CAT), and malondialdehyde (MDA) in an attempt to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Several documents have reported that the inflammatory response and OS are crucial contributors to HSP pathogenesis, 9,[54][55][56] in which the abnormal activation of TLR4 signal get closely involved. 8,19,57 When microorganisms (bacteria, viruses, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several documents have reported that the inflammatory response and OS are crucial contributors to HSP pathogenesis, 9,[54][55][56] in which the abnormal activation of TLR4 signal get closely involved. 8,19,57 When microorganisms (bacteria, viruses, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of HSP have not been fully elucidated, it is currently considered that immune inflammation and oxidative stress (OS) get deeply involved in it, especially the activation of toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88)/nuclear transcription factor-kappa B (NF-κB) signaling way. [7][8][9][10] TLR4 is a key transmembrane protein mediating the inflammatory and OS reaction. It binds to the cytoplasmic adapter molecule MyD88 to activate the NF-κB signal, [11][12][13] which triggers the release of pro-inflammatory factors and chemokines, and the appearance of abnormal oxidative/antioxidant indicators, eg, increased reactive oxygen species (ROS), malondialdehyde (MDA) and nitric oxide (NO), as well as decreased catalase (CAT), glutathione (GSH) and superoxide dismutase (SOD).…”
Section: Introductionmentioning
confidence: 99%